Students’ Perceptions of the Impact of Interactive Technology on Engagement in Science Classes - Alzoubi, Khaled Ahmed Aqeel (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study investigated the impact of interactive technology (IT)—specifically artificial intelligence (AI) tools and virtual reality (VR)—on student engagement within a Jordanian applied technology school in Amman during the first semester of the 2024/2025 academic year. Employing a mixed-methods approach with 126 male students in grades 9–12, the research measured shifts in cognitive, social, reflective, and goal-oriented engagement. Quantitative data from a pre-post survey, analyzed via paired sample t-tests, revealed statistically significant improvements across all engagement dimensions post-intervention. Qualitative insights from focus group discussions illuminated how these technologies fostered deeper understanding, collaboration, and self-regulated learning. The findings are interpreted through the lenses of constructivism and the cognitive-affective-social-behavioral model of engagement. This study concludes that a strategically integrated IT framework can significantly enhance the learning experience, aligning with Jordan’s national educational goals. Recommendations are provided for optimizing technology integration and mitigating potential drawbacks.